Barriers to the success of an electronic pharmacovigilance reporting system in Kenya: an evaluation three years post implementation. (12th October 2017) - Agoro, Oscar O; Kibira, Sarah W; Freeman, Jenny V; Fraser, Hamish S F
Abstract: Objective: Electronic pharmacovigilance reporting systems are being implemented in many developing countries in an effort to improve reporting rates. This study sought to establish the factors that acted as barriers to the success of an electronic pharmacovigilance reporting system in Kenya 3 years after its implementation. Materials and Methods: Factors that could act as barriers to using electronic reporting systems were identified in a review of literature and then used to develop a survey questionnaire that was administered to pharmacists working in government hospitals in 6 counties in Kenya. Results: The survey was completed by 103 out of the 115 targeted pharmacists (89.5%) and included free-text comments. The key factors identified as barriers were: unavailable, unreliable, or expensive Internet access; challenges associated with a hybrid system of paper and electronic reporting tools; and system usability issues. Coordination challenges at the national pharmacovigilance center and changes in the structure of health management in the country also had an impact on the success of the electronic reporting system. Discussion: Different personal, organizational, infrastructural, and reporting system factors affect the success of electronic reporting systems in different ways, depending on the context. Context-specific formative evaluations are useful in establishing the performance of electronic reporting systems to identify problems and ensure that they achieve the desired objectives. Conclusion: While several factors hindered the optimal use of the electronic pharmacovigilance reporting system in Kenya, all were considered modifiable. Effort should be directed toward tackling the identified issues in order to facilitate use and improve pharmacovigilance reporting rates.